PENTINGNYA PENYAMPAIAN INFORMASI YANG TEPAT UNTUK MEMBANGUN KOMUNIKASI EFEKTIF KEPADA SISWA KELAS III SEKOLAH DASAR [THE IMPORTANCE OF DELIVERING INFORMATION APPROPRIATELY IN BUILDING EFFECTIVE COMMUNICATION TO GRADE 3 OF PRIMARY STUDENTS] - Rombean, Chusmiaty; Rahmadi, Pitaya; Appulembang, Oce Datu (JOHME: Journal of Holistic Mathematics Education, 2021)
The communication ability possessed by humans, especially Christians, is used to realize God's will. One of them is in carrying out the real Great Commission in the field of education, especially in the learning process. Learning in the classroom must take place effectively so that learning objectives are achieved through the realization of effective communication. Often, teachers have not been able to build effective communication because teachers are not able to manage the class properly through the delivery of appropriate information and according to the characteristics of student development, so that many students are less serious and disciplined in learning. Therefore, this article aims to discuss the importance of delivering the right information in building effective communication to third grade elementary school students as research subjects in this paper. Based on the results of the study, it was found that teachers experienced problems in managing the class, especially in attracting students' attention, giving instructions, conveying and applying class rules and procedures so that effective communication in classroom management had not been achieved, while in delivering subject matter, effective communication was quite built because students actively involved. Submission of appropriate information is very important for teachers to do, especially in building effective communication because it really determines the success or failure of learning activities by considering the characteristics of student development. Christian teachers also act as facilitators who reflect Christian values in every teaching they do.BAHASA INDONESIA ABSTRACT: Kemampuan berkomunikasi yang dimiliki oleh manusia terutama orang Kristen digunakan untuk mewujudkan kehendak Tuhan. Salah satunya dalam menjalankan Amanat Agung yang nyata dalam bidang pendidikan khususnya dalam proses pembelajaran. Pembelajaran di dalam kelas harus berlangsung dengan efektif agar tujuan pembelajaran tercapai melalui terwujudnya komunikasi efektif. Sering kali, guru belum dapat membangun komunikasi efektif tersebut karena guru tidak mampu mengelola kelas dengan baik melalui penyampaian informasi yang tepat dan sesuai karakteristik perkembangan siswa, sehingga banyak siswa yang kurang serius dan disiplin dalam belajar. Oleh karena itu, artikel ini bertujuan untuk membahas mengenai pentingnya penyampaian informasi yang tepat dalam membangun komunikasi efektif kepada siswa kelas III SD sebagai subjek penelitian dalam makalah ini. Berdasarkan hasil penelitian tersebut, ditemukan bahwa guru mengalami kendala dalam mengelola kelas khususnya dalam menarik perhatian siswa, memberi instruksi, menyampaikan dan menerapkan peraturan dan prosedur kelas sehingga komunikasi efektif dalam pengelolaan kelas belum tercapai, sedangkan dalam penyampaian materi pelajaran, komunikasi efektif cukup terbangun karena siswa terlibat aktif. Penyampaian informasi yang tepat sangatlah penting untuk guru lakukan khususnya dalam membangun komunikasi efektif karena sangat menentukan berhasil atau tidaknya kegiatan pembelajaran dengan mempertimbangakan karakteristik perkembangan siswa. Guru Kristen juga berperan sebagai fasilitator yang mencerminkan nilai-nilai Kristiani dalam setiap pengajaran yang dilakukannya.